A retrospective study of 50 cases of lower limb soft tissue infection and its different modalities of presentation and its management - Sarvaiya, Sagar B.; Patel, Deval M. (International Journal of Research in Medical Sciences, 2022)
Background: Soft tissue infections are common in everyday practice. They show great variations in their severity. Skin and soft tissue infections are usually preceded by minor traumatic events. Among them soft tissue bacterial infections of lower limbs are more common. Patients having diabetes makes the scenario even worst. Diagnosis, intervention and treatment of these infections are very important. This study aims at understanding the pathology involved for lower limb soft tissue infections, spectrum of organisms and different treatment modalities in various age group and gender. Methods: 50 cases of lower limb soft tissue infections were included in this study. Detailed history, clinical examination, investigations, pre-operative preparation, intraoperative details and post-operative management were included. Results: 94% patients were having history of trauma.88% patients were having history of diabetes. Staphylococcus aureus was the most common (43%) organism cultured from swabs followed by pseudomonas (36%) out of total cases. Minimum stay in hospital was of 4 days to a maximum of 34 days. Most of the patients were managed with regular dressing and debridement. Conclusions: The patients sought treatment only when they had extensive lesions which affect their daily living. Health education regarding foot care forms an integral part of surgical management of lower limb soft tissue infections. Readmissions are mainly due to inadequate local control or fluctuating blood sugar levels and improper foot care due to illiteracy, poverty, ignorance and lack of adequate primary care facilities.